Synthesis and Characterization of VO(IV) and UO2(VI) Complexes with Nitrogen and Oxygen Donor Ligands - Viswanathan, M. (Asian Journal of Chemistry, 2016)
A few complexes of VO(IV) and UO2(VI) with two nitrogen and oxygen donor ligands, N,N´-diethylenediamine-bis(3-carboxypropenamide) [DEBCPH2] and N,N´-propylenediamine-bis(3-carboxypropenamide) [PBCPH2] have been synthesized and characterized by chemical analysis, conductance, magnetic, thermal and infrared spectral studies. On the basis of the above studies it is concluded that PBCPH2 acts as tetradentate in both the oxo-vanadium(IV) and dioxouranium(VI) complexes. The complexes have been assigned the formulae [VO(PBCP)]·2H2O and [UO2(PBCP)] respectively. On the other hand, DEBCPH2 acts as tetradentate in the oxovanadium(IV) complex whereas in the dioxouranium(VI) complex it shows pentadentate nature. Thus, these two complexes have been assigned the formulae [VO(DEBCP)]·2H2O and [UO2(DEBCP)] respectively.